2006
DOI: 10.2337/db06-0540
|View full text |Cite
|
Sign up to set email alerts
|

Fat Depot–Specific Characteristics Are Retained in Strains Derived From Single Human Preadipocytes

Abstract: Fat depots vary in size, function, and potential contribution to disease. Since fat tissue turns over throughout life, preadipocyte characteristics could contribute to this regional variation. To address whether preadipocytes from different depots are distinct, we produced preadipocyte strains from single abdominal subcutaneous, mesenteric, and omental human preadipocytes by stably expressing human telomere reverse transcriptase (hTERT). These strains could be subcultured repeatedly and retained capacity for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
186
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(207 citation statements)
references
References 48 publications
17
186
1
3
Order By: Relevance
“…Indeed, intraabdominal/visceral fat accumulation is associated with a higher risk of diabetes and metabolic syndrome, whereas increased s.c. fat in the thighs and hips may even have a protective effect (4,8,26). A growing body of evidence suggests that these depot-specific associations are due to intrinsic differences in the properties of adipocytes in each depot (27,28) and the consequence of a divergence in their developmental origin (1,(9)(10)(11)(12)29). Consistent with this hypothesis, we and others observed high differential expression of developmental genes between intraabdominal and s.c. adipose depots in both rodents and humans (11,12).…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, intraabdominal/visceral fat accumulation is associated with a higher risk of diabetes and metabolic syndrome, whereas increased s.c. fat in the thighs and hips may even have a protective effect (4,8,26). A growing body of evidence suggests that these depot-specific associations are due to intrinsic differences in the properties of adipocytes in each depot (27,28) and the consequence of a divergence in their developmental origin (1,(9)(10)(11)(12)29). Consistent with this hypothesis, we and others observed high differential expression of developmental genes between intraabdominal and s.c. adipose depots in both rodents and humans (11,12).…”
Section: Discussionsupporting
confidence: 75%
“…It has been shown that regardless of the gender, subcutaneous fat decreases and abdominal fat increases with age (Kuk et al 2009). Elevated visceral fat accumulation is strongly associated with ectopic fat deposition in skeletal muscle, heart, liver, pancreas, or blood vessels, a trend leading to lipotoxicity in aged individuals (Slawik and Vidal-Puig 2006;Tchkonia et al 2010;Tchkonia et al 2006). Nonsubcutaneous fat accumulation is known to be strongly associated with insulin resistance and dyslipidemia (Kuk et al 2009).…”
Section: Adipose Tissue and Obesitymentioning
confidence: 99%
“…Isolation and differentiation of adipocyte precursor cells Human preadipocytes were isolated according to the method of Rodbell [15], with minor modifications, and differentiated for about 30 days in DMEM/F-12 medium supplemented with insulin, dexamethasone, triiodothyronine and rosiglitazone, in line with recently published methods for differentiation of human preadipocytes [16]; for further details on preadipocyte isolation and differentiation, see ESM. Differentiation of cells into adipocytes was assessed through morphological analysis and Oil-Red-O staining.…”
Section: Methodsmentioning
confidence: 99%